Penyelesaian Wanprestasi Dalam Perjanjian Kerja PT. Sukses Bintang Indonesia Dengan PT. Ratu Intan Mining (Studi Kasus Putusan Nomor 3854/K/Pdt/2022) - Melosia Mangiwa, Devina; Djajaputra, Gunawan (LPPM Universitas Ekasakti Padang, 2024)
This article provides an overview of the implementation of an employment agreement or employment contract in the business world that often causes interpretation. This research is based on normative legal research with qualitative research methods. The results of this study describe the causes of default in an agreement which as a result can harm the parties who bind themselves in an agreement. Settlement of default can basically be reached through several legal remedies such as sending a subpoena, negotiations to the lawsuit in the trial. As the decision of the panel of judges in a civil case between PT. Sukses Bintang Indonesia and PT. Ratu Intan Mining has resolved the dispute between the parties in accordance with the provisions of applicable regulations.